Exploring the Influence of Social Media Utilization on Enhancing TOEFL Proficiency among Medical Students - Syahputra, Bambang Panca; Sagala, Rakhmat Wahyudin; Amri, Yusni Khairul (BIRCU, 2023)
This study delves into investigating the impact of social media utilization on enhancing TOEFL proficiency among medical students. In an era where digital platforms have revolutionized communication and learning, this study examines how integrating social media tools into language learning environments can contribute to a more engaging and relevant educational experience. The focus on medical students is particularly pertinent, given the critical role adequate English language proficiency plays in their future medical careers, where precise communication is essential. The researchers used a descriptive survey design because this study aimed to obtain detailed information about the use of Social Media (SM) in improving TOEFL proficiency from medical students' perspective. The study included 46 students, with 15 of them being men (32.61%) and 31 women (67.39%). Participants were asked to complete an electronic questionnaire distributed through their subject's WhatsApp group voluntarily. For medical students, social media platforms can be incredibly beneficial to enhance their TOEFL learning experience. These platforms offer a broader range of communication and interaction opportunities that can aid in improving English proficiency. Furthermore, utilizing social media can assist in integrating the language into daily life. The future research will be especially beneficial for students who are not majoring in English, as it will enable them to overcome their fears and improve their overall learning experience in English as a Foreign Language.